Functional pain disorders - Mayer, Emeran (Henry Stewart Talks, 2009)
Visceral pain disorders, Epidemiology of IBS, Overlap of IBS with other functional pain syndromes, Is there a shared CNS abnormality in functional pain disorders?, Reported alterations in brain responses in stress-sensitive pain syndromes, Deconstructing the clinical syndrome into biological endophenotypes, Identifying associations between genes and biological intermediate phenotypes, Central neurobiological phenomics strategy, Temporal dimensions of central pain amplification, Central pain amplification: altered sensorimotor gating, Preattentive sensory gating mechanisms, Role of altered emotional arousal, Central pain amplification
Archived at 2021/02/25